Nilai Sustainability dan Women Empowerment dalam Akun Instagram @rubicommunity sebagai Kampanye Brand Avoskin - Andini Amalia Azroh; Ratih Pandu Mustikasari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study aims to analyze the values of sustainability and women empowerment in Instagram @rubicommunity content. The method used is content analysis with a descriptive quantitative approach. The sample consisted of 89 contents selected using a systematic random sampling technique for the period January 2021 – April 2025. The results showed that the value of women empowerment was more dominant with 44 content or 49%, while the value of sustainability appeared in 29 content or 33%. The value of women's empowerment is raised through two categories of self-development and psychosocial support, while sustainability is present in three categories, namely education and real environmental action, social involvement and community responsibility (CSR), and access to social networks and community support. Avoskin's campaign strategy through the RUBI community shows the brand's consistency in conveying social and environmental messages simultaneously through social media.